Decolonizing children's agency: Perspectives of children in an Urdu-speaking Bihari camp in Bangladesh. (August 2022) - Afroze, Jiniya
Drawing on nine months of ethnographic fieldwork with children and adults in an Urdu-speaking Bihari camp in Bangladesh, this paper critically explores the ambiguities, nuances, and messiness of children's everyday lives and the complex ways in which children negotiate and exercise their agency. With a critical and reflexive analysis of children's experiences in everyday lives, this paper aims to make a meaningful contribution to the knowledge of childhood and children's everyday lives in the majority world context by focusing on an under-researched minority within Bangladesh.